Discussion on Criminalization of Corporate Liability in the Russian Federation - SHASHKOVA, A.V. (Journal of Advanced Research in Law and Economics; Vol 10 No 5 (2019): JARLE Volume X Issue 5(43) Fall 2019, 2019)
The goal of the present research is to formulate scientifically grounded suggestions on the issue of criminalization of corporate liability in Russia. The article focuses on different theoretical approaches towards establishing corporate criminal liability in national legislature of the Russian Federation. The article focuses on the roots and evolution of the problem of introducing criminal corporate liability, analyses arguments pro et contra corporate criminal liability as an instrument of prevention and combat against corporate and other forms of white-collar crime, particularities of implementation of criminal liability for corporations to the legislation of the Russian Federation. The article analyses such symbolic court precedents as those elaborated in cases ‘Santa Clara County v. Southern Pacific Railroad Co.’ in the USA and ‘Salomon v. Salomon & Co. Ltd’. in the UK. The problem of the emergency of the idea of criminalization of corporate responsibility is analyzed from historical point of view with application of the historical method and of the object of the analysis method. Some public-private research methods are also used: formally-logical or comparative legal method are used to compare decisions of different courts on the same precedent. The central part of the article examines different theoretical and practical views on introduction of corporate liability in general and in the Russian Federation in particular. The author aims to shed light on different dimensions of the matter, pointing to interdependency of various aspects.  The analysis of the historical roots of the problem of liability of corporations, introduction of different types of liability in foreign countries, analysis of the position of the civil society and the state bodies in the Russian Federation gives a ground for further elaboration together with the professional society on the problem of necessity of criminal liability for corporations in the Russian Federation to find optimal solution.